Response Surface Optimization of the Treatment of Pharmaceutical Wastewater Using Snail Shell Powders a Natural Coagulant - , Anyikwa Sylvester O.; , P.C Nnaji.; , O.D Onukwuli.; , Edwin Ikezue.; , Chigoziri N. Njoku.; , Chinwendu Umeojiakor T.; , Onwuchewa Chidiebere (Archives of Current Research International, 2025)
This study investigated the treatment of pharmaceutical wastewater from an industry in New Owerri, Imo State, using snail shell powder as a natural coagulant. The wastewater, characterized at the National Soil, Plant, and Water Laboratory, Federal Ministry of Agriculture and Rural Development, Umuahia, Abia State, was treated to reduce turbidity and enhance environmental safety. Chitosan extracted from snail shell was characterized using Energy-Dispersive X-ray Spectroscopy (EDX) and served as the bio-coagulant, leveraging its cost-effectiveness, local availability, and biodegradability. The EDX analysis of the snail powder reveal a calcium carbonate-dominated composition (48.87 wt% Ca, 18.45 wt% O), this indicate that snail shell is suitable additive for bio-coagulant. Response surface methodology optimized the coagulation process, evaluating pH (2–6), coagulant dosage (0.1–2.0 g), and stirring time (5–60 minutes). The highest turbidity removal of 69.7% was achieved at pH 6, 0.1 g coagulant, and 60 minutes, transforming the wastewater from dark brown to light brown. The quadratic model adequately Predicted the Response and the considered factors. These findings demonstrate snail shell’s potential as an eco-friendly alternative to chemical coagulants, supporting sustainable wastewater management in Nigeria’s pharmaceutical sector.